Dislocation and Resettlement in Development : From Third World to the World of the Third. - Chakrabarti, Anjan (Routledge studies in development and society., 2009)
This book offers a unique theory of dislocation in the form of primitive accumulation. It develops a framework that offers alternative avenues to rethinking dislocation and resettlement, and indeed the very idea of development.